Nalbuphine alleviates inflammation by down-regulating NF-κB in an acute inflammatory visceral pain rat model - Dijiao Ruan; Yuanyuan Wang; Sisi Li; Chao Zhang; Wenwen Zheng; Cong Yu (BMC, 2022)
Abstract Introduction Nalbuphine can relieve patients' inflammation response after surgery compared to other opioid drugs. However, its molecular mechanism has not been clear. Activation of NF-κB signaling pathway under oxidative stress and inflammation can maintain pain escalation. Methods We firstly investigated the effect of nalbuphine on writhing test and mechanical allodynia using a rat model of inflammatory visceral pain (acetic acid (AA) administrated). Cytokines (including tumor necrosis factor (TNF)-α, Interleukin (IL)-1β, IL-2, and IL-6 in plasma were tested with ELISA technology. Expression levels of TNF-α, IκBα and p-NF-κB p65 at the spinal cord (L3-5) were measured by western blot or RT-qPCR. Results We found that the paw withdrawal threshold (PWT) values of rats were reduced in the model group, while the numbers of writhing, levels of IL-1β, IL-2, IL-6, and TNF-α in plasma, and p-NF-κB protein and its gene expressions in the lumbar spinal cord were up-regulated. Subcutaneously injection of nalbuphine (10 μg/kg) or PDTC (NF-κB inhibitor) attenuated acetic acid-induced inflammatory pain, and this was associated with reversal of up-regulated IL-1β, IL-2, IL-6, and TNF-α in both plasma and spinal cord. Furthermore, acetic acid increased p-NF-κB and TNF-α protein levels in the white matter of the spinal cord, which was attenuated by nalbuphine. These results suggested that nalbuphine can significantly ameliorate inflammatory pain via modulating the expression of NF-κB p65 as well as inflammation factors level in the spinal cord. Conclusion In conclusion, nalbuphine inhibits inflammation through down-regulating NF-κB pathway at the spinal cord in a rat model of inflammatory visceral pain.